Genetic Association Between Single Nucleotide Polymorphisms of the HLA-G Gene and Papillary Thyroid Carcinoma in Iraqi Patients - Aljanabi, Noor H.; Abed, Reema M. (Iraqi Journal of Science, 2024)
This study was designed to investigate the relationship between HLA-G gene SNPs in exons 2 and 8 and papillary thyroid carcinoma (PTC). Blood samples from 100 patients, categorized into pre- and post-radioactive therapy groups, and 50 healthy subjects were analyzed via PCR and direct sequencing for allele and genotype frequencies. PTC was eight times more prevalent in women. Thyroid assessment hormones exhibited reduced T3 levels pre- and post-radioactive iodine therapy and increased T4 levels post-therapy (49.80 ng/ml vs. control 16.84 ng/ml). Notably, TSH levels significantly decreased before and after therapy in PTC patients versus controls (P = 0.005). HLA-G gene SNPs were linked to PTC risk: in exon 2, genotype AA posed risk (OR = 16.10 and 10.58; P = 0.001) pre- and post-therapy, while homozygous TT in exon 8 increased risk (OR = 7.30; P = 0.001; OR = 4.41; P = 0.018), and heterozygous CT was protective (OR = 0.27; P = 0.016) before therapy. These findings suggest homozygous SNPs contribute to the genetic risk factors for PTC in the Iraqi population.